1988
DOI: 10.4319/lo.1988.33.3.0458
|View full text |Cite
|
Sign up to set email alerts
|

Records of riverbome turbidity currents and indications of slope failures in the Rhone delta of Lake Geneva

Abstract: Records of riverbome turbidity currents and indications of slope failures in the Rhone delta of Lake GenevaAbstract-The sublacustrine topography of the Rhone delta in Lake Geneva is characterized by a channel that can be traced about 9 km beyond the mouth of the river. Two instrumented moorings were deployed from June to August 198 5 in the channel axis at depths of 150 and 20 1 m to detect underflows of dense, sediment-laden river water. Each array consisted of three current meters and a thermistor chain. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 3 publications
2
75
0
1
Order By: Relevance
“…Because Massangla and Pur rivers are temporary torrential tributaries draining steep slopes, dark-coloured SEs in Lake Ledro likely reflect flash flood events (Lambert and Giovanoli, 1988;Bornhold et al, 1994;Gilli et al, 2013). The large flood deposit marked by dark-coloured SE J is thick enough to be mapped along seismic profiles (Fig.…”
Section: Dark-coloured Ses and Flood Depositsmentioning
confidence: 99%
“…Because Massangla and Pur rivers are temporary torrential tributaries draining steep slopes, dark-coloured SEs in Lake Ledro likely reflect flash flood events (Lambert and Giovanoli, 1988;Bornhold et al, 1994;Gilli et al, 2013). The large flood deposit marked by dark-coloured SE J is thick enough to be mapped along seismic profiles (Fig.…”
Section: Dark-coloured Ses and Flood Depositsmentioning
confidence: 99%
“…Comparison between these systems suggests a continuum of progressively better developed submarine channels (Conway et al 2012), so that work at these locations can address questions about flow dynamics in sinuous channels (research direction D below), as well as work on societal risk due to tsunami hazards from delta-front collapse. (2) Lake Geneva in Switzerland and France was where turbidity currents were first noted by Forel (1885) and have cut well developed channel systems (Hsü and Kelts 1985;Lambert and Giovanoli 1988;Girardclos et al 2012). The Rhône delta represents a river-fed system where hyperpycnal river outflows often plunge and allows comparisons to be made between marine and freshwater systems.…”
Section: Suggestions For Key Future Research Directionsmentioning
confidence: 99%
“…The author concluded that the modern canyon is due to sediment erosion by this current and to deposition of sediments on the canyon shoulders. These density currents, with velocities of up to 1 m/s, have been measured in situ by Lambert and Giovanoli (1988) at a water depth of 150 m, almost a century after the work of Forel. These authors also put forward the role of sediment suspensions in turbidity currents, due either to the river input or to the detachment of unstable sediment deposits on the canyon walls.…”
Section: Introductionmentioning
confidence: 99%